2009
DOI: 10.1080/09593330802421458
|View full text |Cite
|
Sign up to set email alerts
|

Non‐destructive monitoring of nitrate concentration in a laboratory flow experiment using time domain reflectometry (TDR)

Abstract: Nitrates, when found in excess in the groundwater, are a health hazard. Nitrates can easily be transported by groundwater movement and may eventually reach aquifers located far away from the contamination location. Recent research has focused on developing innovative techniques to remediate nitrate-contaminated soils. It is important to monitor the nitrate movement in the groundwater to predict the extent of nitrate contamination. Traditionally, nitrate movement is monitored by sampling soil pore water and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The use of TDR probes allows the estimation of available soil nitrogen and immobilised N in non-saline soils (De Neve and Hofmann 2001), and further calibration and development of specific TDR instruments could extend the use of this method, which has so far been limited to experimental work on study farms. The time and the frequency of a reflected TDR wave in the soil depends on its water content and on the quality and quantities of the ions in it, while mathematical models can be built to use the quality of the reflected wave to calculate the concentration of such ions (Krishnapillai andSri Ranjan 2009, Souza et al 2006). However, an extended comparison between chemical and EC based N measurements has proved how only the first one can give a constant reliable assessment of N soil (Baumgarten 2006), and factors such as soil texture, organic matter and stone content can influence the accuracy of results.…”
Section: Methods Based On Soil Mineral N Contentmentioning
confidence: 99%
“…The use of TDR probes allows the estimation of available soil nitrogen and immobilised N in non-saline soils (De Neve and Hofmann 2001), and further calibration and development of specific TDR instruments could extend the use of this method, which has so far been limited to experimental work on study farms. The time and the frequency of a reflected TDR wave in the soil depends on its water content and on the quality and quantities of the ions in it, while mathematical models can be built to use the quality of the reflected wave to calculate the concentration of such ions (Krishnapillai andSri Ranjan 2009, Souza et al 2006). However, an extended comparison between chemical and EC based N measurements has proved how only the first one can give a constant reliable assessment of N soil (Baumgarten 2006), and factors such as soil texture, organic matter and stone content can influence the accuracy of results.…”
Section: Methods Based On Soil Mineral N Contentmentioning
confidence: 99%
“…Calculated electrical conductivity of the pore water has been used to determine soil salinity (Bouksila et al, 2008;Zhang et al, 2004). Several studies have successfully demonstrated the potential to estimate nitrate (NO 3 ) concentration of soil solution from electrical conductivity measurement using time domain reflectometry (TDR) sensors (Krishnapillai and Ranjan, 2009;Payero et al, 2006;Nissen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Dalton et al (1984) fi rst demonstrated the use of the TDR method for simultaneous measurement of soil moisture content and bulk electrical conductivity (EC). Later, the probes were adapted for continuous monitoring of NO 3 -N or other ionic solutes in soil and water in both laboratory and fi eld experiments (Nissen et al, 1998;Das et al, 1999;De Neve et al, 2003;Payero et al, 2006;Krishnapillai and Sri Ranjan, 2009). Th e operational principals and recent advancements in dielectric and EC measurements using TDR were reported by Robinson et al (2003).…”
Section: Estimating Soil Solution Nitrate Concentration From Dielectrmentioning
confidence: 99%
“…Th e conductive behavior of soils has also been used by other methods, particularly the time domain refl ectometry (TDR) technique, to predict pore water NO 3 -N concentrations (Das et al, 1999;Krishnapillai and Sri Ranjan, 2009). Originally TDR probes were used to estimate the VWC of the soil by measuring the relative permittivity of the medium (Topp et al, 1980).…”
Section: Estimating Soil Solution Nitrate Concentration From Dielectrmentioning
confidence: 99%